1987
DOI: 10.1038/329742a0
|View full text |Cite
|
Sign up to set email alerts
|

Genome reshuffling of the copia element in an inbred line of Drosophila melanogaster

Abstract: Mobile genetic elements are found in the genomes of many organisms, and because of their effects on genes and their ability to induce chromosomal rearrangements they are an important source of genetic variability. Transposition rates are usually found to be low, estimated at around 10(-3) per generation. Higher rates of transposition are observed, however, in crosses between certain strains of Drosophila melanogaster ('hybrid dysgenesis'), which can lead to a dramatic rearrangement of many mobile elements ('tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 19 publications
1
33
0
1
Order By: Relevance
“…We observed reversions of some previously fixed insertions in our experiment that might have caused partial rescue of fitness. Excisions of copia have been seen in one other experiment (Biemont et al, 1987). Excisions of other retrotransposons also seem to be rare (Belyaeva et al, 1982 ;Kim & Belyaeva, 1991;Nuzhdin & Mackay, 1994 ;Maside et al, 2000).…”
Section: (Iii) Tes In Mutation-accumulation Experimentsmentioning
confidence: 85%
See 1 more Smart Citation
“…We observed reversions of some previously fixed insertions in our experiment that might have caused partial rescue of fitness. Excisions of copia have been seen in one other experiment (Biemont et al, 1987). Excisions of other retrotransposons also seem to be rare (Belyaeva et al, 1982 ;Kim & Belyaeva, 1991;Nuzhdin & Mackay, 1994 ;Maside et al, 2000).…”
Section: (Iii) Tes In Mutation-accumulation Experimentsmentioning
confidence: 85%
“…The rate of copia excision (owing to either precise or imprecise deletions) is interesting because of its rarity (Biemont et al, 1987;Pasyukova & Nuzhdin, 1993 ;Nuzhdin & Mackay, 1994). We detected the first copia excision from site 30A in generation 22 (no hybridization in six larvae of one MA replicate).…”
Section: (Iv) Transpositions Of Copia In Line 39mentioning
confidence: 85%
“…Finally, it should be noted that in three cases we found two additional neoRT copies in G418-resistant clones. Future evaluation of the significance of these unexpected structures will have to take into account that transposition (i) might be highly mutagenic for the retrotransposon as observed in yeast for Tyl (6) and (ii) under given circumstances might be a frequent and/or cooperative event as observed in Drosophila (17)(18)(19) …”
Section: Discussionmentioning
confidence: 99%
“…First, how can it be demonstrated that putative transposons actually transpose in mammalian cells; in particular, are proviral copies of the retrovirus able to transpose? Second, is transposition modulated by genetic or epigenetic factors as observed in Drosophila and yeast (6,(17)(18)(19)? Third, can transposition be implicated in tumorigenic processes?…”
Section: Introductionmentioning
confidence: 99%
“…One surprising result was the observation of transposition bursts of TEs such as Doc (a non-LTR retrotransposon; Gerasimova et al 1990), copia (a retrotransposon; Biémont et al 1987;Gerasimova et al 1990;Pasyukova and Nuzhdin 1993), and P (a DNA transposon; Biémont et al 1990) while inbred lines were being maintained in the laboratory. Although we did not know whether this mobilization was the result of the inbreeding itself, or simply ''spontaneous'' transposition revealed by the homozygosity of the lines, which made it easier to observe new insertions, we were forced to conclude that inbred lines were not as homozygous as expected, at least with regard to TE insertions.…”
Section: Transposable Elements As Components Of Genetic Diversitymentioning
confidence: 99%